Description Of Attitude And Consumer Purchasing Decisions Against Red Rice - Nana Trisna Mei Br Kabeakan (JASc (Journal of Agribusiness Sciences), 2020)
The majority of Indonesian people consume rice as a daily staple food and the much consumed rice comes from white rice. Besides white rice, one type of rice is red rice. Red rice is included in broken rice skin which has advantages compared to white rice found in its nutritional composition and also consumes red rice is effective for reducing total cholesterol levels of type 2 DM patients. The purpose of this study is to describe the attitudes and purchasing decisions of consumers towards brown rice . Respondents in this study were 100 people. Data analysis was performed using descriptive statistical analysis. The results showed that respondents had a positive attitude towards red rice with an average respondent's answer on all attitude statements was 4.34 which means it was in the category of strongly agree and the respondents' buying decision was 3.93 which means it was in the agreed category